TRANSFORMATION OF RURAL POPULATION VITAL STRATEGIES - Morekhanova, Marina (Economics of Agriculture, 2018)
Transformation of rural population vital strategies and current period peculiarity of its adaptation to economic reforms in agribusiness are analyzed in this paper. Special attention is dedicated to the problems of readiness of different social groups to new professional knowledge acquisition, their commitment in it, and to analysis of modern life strategies and employment preferences of rural youth. The paper is based on sources of sociological researches conducted by the Institute of Agrarian Problems of the Russian Academy of Sciences with personal involvement of the author in one of the Russian regions (Saratovs oblast) in 1993- 2007, dedicated to the problems of rural community adaptation to changing socioeconomic conditions. The research included polls, budget studies, and "deep" interviews with the budget study respondents.